Sustainability of water and sanitation state-owned companies in Brazil. Issue 2 (June 2022) - Gonçalves, Edson; Werneck Capodeferro, Morganna; Jerônimo Smiderle, Juliana; Engel Guimarães, Pedro H.
This paper assesses the sustainability of Brazilian's water and sanitation state-owned companies' services. The assessment was conducted based on the selection of six indicators reflecting three of the sustainability dimensions: social, economic, and environmental. We built a global sustainability index by adopting the MACBETH multicriteria analysis methodology, which aggregates the dimensions of sustainability with their respective indicators. As main result we found that two companies were considered sustainable in each of the three assessed dimensions of sustainability, and that three companies were globally sustainable according to the methodology applied in this study. Setting sustainability targets and increasing regulatory enforcement leads to improved services performance. Further, sustainable sanitation services bring us closer to achieving the national targets for universal access and Sustainable Development Goal 6 established by the United Nations.